Hydrodynamic performance of a submersible net cage integrated with an offshore platform - Tian, Zhenglin; Yang, Hui; Wen, Hongjie (Frontiers in Marine Science, 2024)
The integrated development of offshore platform and net cage is a significant concern in ocean engineering. To optimize cost-effectiveness and maximize the utilization of limited ocean space resources, a composite structure is proposed, which integrates a submersible net cage onto the steel pipe piles of offshore platform. Based on the OpenFOAM software package, a numerical model is developed to assess the hydrodynamic performance of this composite structure. In this model, the net cage is simplified as a closed box structure comprising six planar nets, with each planar net further represented as a porous structure based on equivalent resistance. The model is validated by comparing the predicted results with the relevant experimental and numerical data. Subsequently, the model is employed to comprehensively investigate the hydrodynamic performance of the submersible net cage integrated with an offshore platform. Velocity variations inside and outside the net cage are analyzed under various wave-current conditions. Additionally, the forces exerted on the steel pipe piles by the net cage at different submerged depths are also examined.